The identification of yield components, genetic variability, and heritability to determine the superior cocoa trees in West Papua, Indonesia - ANTONIUS SUPARNO; M. A. ARBIANTO; SARASWATI PRABAWARDANI; PAULUS CHADIKUN; HERMAN TATA; FIONA DJUNITA NATALIA LUHULIMA (Society for Indonesian Biodiversity, 2024)
Abstract. Suparno A, Arbianto MA, Prabawardani S, Chadikun P, Tata H, Luhulima FDN. 2024. The identification of yield components, genetic variability, and heritability to determine the superior cocoa trees in West Papua, Indonesia. Biodiversitas 25: 2363-2373. One of the obstacles to increasing the productivity of cocoa is the existence of superior cocoa clones. This research, therefore, was carried out to select the superior cocoa tree candidates from the existing cocoa plantation populations over 30 years old, using a descriptive method on the yield components of superior cocoa candidates in PT. Cokran Cocoa Plantation, South Manokwari. This research was conducted from May 2020 to May 2022. The initial information on 32 superior cocoa trees was obtained from the farmers who were involved and worked at the PT. Cokran Cocoa Plantation for 30 years. Cocoa was planted on an area of 1,680 ha with a spacing of 2 x 4 m. Data on the 13 quantitative characters of the cocoa pod and cocoa beans were analyzed using ANOVA (SAS V.9 For Window). These 13 quantitative data, including 11 qualitative data of leaves and fruit were used to analyze the relationship of kinship pattern among the accessions using NTSys ver. 2.1. Results of the research show that 8 cocoa accessions had a high production potential of more than 6,000 g per tree annually, namely CKR-02, CKR-03, CKR-04, CKR-09, CKR-12, CKR-26, CKR-28, and CKR-41 accessions. Accessions that produced 1,000 g of dry cocoa beans in less than 20 pods were CKR-03, CKR-04, CKR-07, CKR-09, CKR-12, CKR-15, CKR-22, CKR-26, CKR-40, and CKR-41. Candidate cocoa clones that have the potency to produce dry cocoa beans with grade AA quality were CKR-03, CKR-04, CKR-12, CKR-26, CKR-40, and CKR-41. Wide phenotypic and genotypic coefficients of variations were found among the 32 accessions. High heritability was produced by pod length, pod girth, pod fresh mass, seed number/pod, seed fresh mass, and seed dry mass. The cluster analysis showed a wide morphological diversity of the 32 cocoa accession candidates based on the yield component characters.